HELP LDL Apheresis Reduces Plasma Pentraxin 3 in Familial Hypercholesterolemia - Zanetti, Michela (Public Library of Science, 2014)
BACKGROUND: Pentraxin 3 (PTX3), a key component of the humoral arm of innate immunity, is secreted by vascular cells in response to injury, possibly aiming at tuning arterial activation associated with vascular damage. Severe hypercholesterolemia as in familial hypercholesterolemia (FH) promotes vascular inflammation and atherosclerosis; low-density lipoprotein (LDL) apheresis is currently the treatment of choice to reduce plasma lipids in FH. HELP LDL apheresis affects pro- and antiinflammatory biomarkers, however its effects on PTX3 levels are unknown. We assessed the impact of FH and of LDL removal by HELP apheresis on PTX3. METHODS: Plasma lipids, PTX3, and CRP were measured in 19 patients with FH undergoing chronic HELP LDL apheresis before and after treatment and in 20 control subjects. In the patients assessment of inflammation and oxidative stress markers included also plasma TNFα, fibrinogen and TBARS. RESULTS: At baseline, FH patients had higher (p = 0.0002) plasma PTX3 than matched control subjects. In FH PTX3 correlated positively (p≤0.05) with age, gender and CRP and negatively (p = 0.01) with HELP LDL apheresis vintage. The latter association was confirmed after correction for age, gender and CRP. HELP LDL apheresis acutely reduced (p≤0.04) plasma PTX3, CRP, fibrinogen, TBARS and lipids, but not TNFα. No association was observed between mean decrease in PTX3 and in LDL cholesterol. PTX3 paralleled lipids, oxidative stress and inflammation markers in time-course study. CONCLUSION: FH is associated with increased plasma PTX3, which is acutely reduced by HELP LDL apheresis independently of LDL cholesterol, as reflected by the lack of association between change in PTX3 and in LDL levels. These results, together with the finding of a negative relationship between PTX3 and duration of treatment suggest that HELP LDL apheresis may influence both acutely and chronically cardiovascular outcomes in FH by modulating PTX3.